2022
DOI: 10.12911/22998993/145290
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Electrocoagulation Process in Removing Organic and Nitrogenous Compounds from Landfill Leachate in a Three-Compartment Reactor

Abstract: In this study, the effectiveness of the electrocoagulation (EC) process was evaluated based on the reduction of organic and nitrogenous contaminants in landfill leachate. A three-compartment electrochemical reactor as pre-treatment of stabilized landfill leachate was carried out ahead of biological treatment. The removal efficiencies of COD, BOD, ammonia, and nitrate were analyzed at pH 4, 6, and 8 with the current densities of 20.83 and 29.17 mA•cm -2 . At pH 4, the highest removal of COD and NH 4 + was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
3
2
Order By: Relevance
“…Research by Maliki et al (2020) showed that the use of electrocoagulation can decrease TDS levels by up to 25.64% from the initial value. This decrease is lower than the results of the study by Bagastyo et al (Bagastyo et al, 2022), where TDS levels can drop by up to 49% through the same process. TDS levels tend to decrease during the electrocoagulation process, although initial readings are not always consistent due to settling and sedimentation (Idusuyi et al, 2022).…”
Section: Conductivity and Tdscontrasting
confidence: 75%
“…Research by Maliki et al (2020) showed that the use of electrocoagulation can decrease TDS levels by up to 25.64% from the initial value. This decrease is lower than the results of the study by Bagastyo et al (Bagastyo et al, 2022), where TDS levels can drop by up to 49% through the same process. TDS levels tend to decrease during the electrocoagulation process, although initial readings are not always consistent due to settling and sedimentation (Idusuyi et al, 2022).…”
Section: Conductivity and Tdscontrasting
confidence: 75%
“…The percentage decrease in the TDS value was 65.3%. The decrease in the TDS value was higher than the value obtained by Bagastyo et al [13] (49%) but lower than those obtained by Bakry et al [11,14,15] (78%, 70.40%, and 91.50% respectively). According to Galvo et al [16] Guo et al [17] there are several factors that affect the result of electrocoagulation, which are the material and shape of the anode, pH, current density, electrode distance, conductivity, current strength, electrocoagulation time and power.…”
Section: Effect Of Electrolysis Time On Total Dissolved Solid (Tds)contrasting
confidence: 64%
“…Several studies have reported the EC can be used to decrease nitrate concentration. Malakootian et al [56,57] report 89.7% and 43-59% removal of nitrate, respectively. This happens because an oxidation reaction occurring at the anode produces cation metals that can eliminate nitrate from water [58].…”
Section: Nitrite (No2) and Nitrate (No3)mentioning
confidence: 97%